Upaya Penurunan Permasalahan Missing Part dan Missing Hardware pada PT. X - Cindy Felicia; Prayonne Adi; Tan Siu Kwang (Jurnal Titra, 2022)
PT. X is a wooden furniture manufacturing company that produces two types of products: knockdown and set-up, with a make-to-order system. Customer complaints in 2021 show that knockdown products are prone to experiencing the three biggest defects: broken/damage (34.2%), missing parts (25.5%), and missing hardware (21.0%). This research will focus on two types of defects: missing parts and missing hardware in knockdown products. This research aims to discover root cause and solution to overcome the defective product that passed into the customer's hands. This study utilizes two quality improvement tools: pareto chart and 5 whys analysis, which found four root causes of missing parts and five root causes of missing hardware. Solutions to overcome missing parts problems are Working List Packing, and Standard Operating Procedure (SOP) for incomplete packing. Meanwhile, solutions to overcome the missing hardware problem are Working List Packing Hardware, installation of ventilators, and procurement of hardware charging systems.